Nursing interventions of choice for the prevention and treatment of suicidal behaviour: The umbrella review protocol - Teresa Sufrate‐Sorzano; Raúl Juárez‐Vela; Carmen Amaia Ramírez‐Torres; Félix Rivera‐Sanz; María Elena Garrote‐Camara; Pastells‐Peiró Roland; Montserrat Gea‐Sánchez; Pablo Del Pozo‐Herce; Vicente Gea‐Caballero; Beatriz Angulo‐Nalda; Iván Santolalla‐Arnedo (Wiley, 2022)
Abstract Aim To determine which interventions, from a nursing perspective, can be considered as the interventions of choice for the prevention and treatment of suicidal behaviour. In this way, the umbrella review attempts to identify nursing interventions from the Nursing Interventions Classification (NIC) taxonomy with evidence for this purpose. Design Descriptive study protocol. Methods This umbrella review will consist of an extensive, systematic search of published systematic reviews and meta‐analyses of studies examining interventions of choice for the prevention and treatment of suicidal behaviour. A systematic search of papers indexed in PubMed, CINAHL, Cochrane Database of Systematic Reviews, Scopus, ISI Web of Knowledge and the Joanna Briggs Institute databases will be carried out; the results will be evaluated for inclusion by two independent reviewers. In addition, the bibliographic references of the included reviews will be searched. The assessment of the methodological quality of the included systematic reviews and meta‐analyses, and data extraction, will be performed by two independent reviewers. Conflicts between reviewers will be resolved by an independent third reviewer. Research Ethics Committee approval is not required for this umbrella review. Results We will determine which of the interventions identified as being of choice in the review are included in the Nursing Interventions Classification (NIC); they may be an effective therapeutic tool for nurses in the prevention and treatment of suicidal behaviour.